Analisis Strategi Penyusunan ATP Berbasis CP dalam Kegiatan Microteaching Mahasiswa Calon Guru Sekolah Dasar - Yuni Hajar; Nurmayani Nurmayani; Ira Sihotang; Talenta Siahaan; Jogian Sibatuara; Meita Lumban Gaol; Nomensius Purba; Irma yani Panjaitan; Putri Erika Sianturi (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to describe the strategy for developing the Learning Objective Flow (ATP) based on Learning Outcomes (CP) in fourth-grade microteaching activities at SD Negeri 060879. The study was conducted due to students’ difficulties in transforming general CP into specific, measurable learning objectives aligned with elementary school students’ characteristics. A qualitative descriptive method was used, involving a fourth-grade teacher as the informant. Data were collected through interviews, observation, and documentation, and analyzed using the Miles and Huberman model. The findings show that the main difficulties lie in analyzing CP into ATP, selecting operational verbs, and aligning objectives with learning activities and assessments. The implementation of a systematic CP analysis strategy makes ATP development clearer, more structured, and more appropriate to students’ developmental levels. This strategy also helps students design more effective and varied learning activities. In conclusion, CP-based ATP development can improve the quality of teaching modules and support successful microteaching implementation.